The instability effect of constant power loads - Jusoh, Awang (IEEE, 2004)
The sub-system interaction and instability phenomena is a common problem in the Distributed Power System (DPS). The interaction arises because each individual converter has internal control function such as to regulate the converter output voltage, which results in the converter tends to draw a constant power and therefore has a negative incremental input impedance. The constant power and negative input resistance characteristic potentially have a de-stabilising effect on the electrical supply system. The paper presents the analysis, theoretical design and simulation of a simple DC DPS. The analysis of the LC fitter and its damping parameters were given. The effect of the negative input resistance of the CPL on the filter was analysed using small signal input resistance of the load. The passive damping method was used to reduce the system interaction between the converters. The results were verified by MATLAB Simulink simulation.